PAM1 regulates meiosis by coupling RNA processing to the chromosome axis - Qian Du; Minghui Wang; Choon-Lin Tiang; Moira J. Sheehan; Paul Altendorf; Ju-Kyung Yu; Otto Hudecz; Elisabeth Roitinger; Chung-Ju Rachel Wang; Robert Bukowski; Robert B. Meeley; Clint Ko; et al. (Proceedings of the National Academy of Sciences, 2026)
Meiosis is a fundamental process responsible for sexual reproduction and generating genetic diversity in the progeny. Its successful completion requires fine-tuning of expression programs of many genes: promoting expression of genes involved in meiotic processes and suppressing genes whose expression may interfere with meiosis. Molecular mechanisms involved in meiotic transcriptome regulation and controlling meiosis progression vary between plants, animals, and fungi and remain elusive. We found that the Plural abnormalities of meiosis1 ( Pam1 ) gene in maize controls meiosis progression by tethering transcriptome processing to the meiosis-specific chromosome axis. Pam1 encodes an RNA binding protein that becomes associated with chromosomes during early meiotic prophase I, binds transcripts of a large number of meiosis-related genes, and affects their splicing by interacting with the CCR4-NOT RNA processing protein complex. Disrupting Pam1 function results in a wide array of severe meiosis defects affecting chromosome condensation and dynamics, nuclear envelope and cytoskeleton organization, as well as the overall meiosis progression. Pam1 controls only a subset of meiotic genes and processes, indicating that several programs directing transcriptome architecture collectively regulate meiosis. RNA-binding proteins have been found to control meiosis progression in fungi and animals, and it is now shown to be also the case in plants. Interestingly, these proteins all exhibit distinct modes of action and evolutionary origins, presenting a remarkable case of convergent evolution. Uncovering mechanisms controlling meiosis progression should enable engineering meiosis to benefit crop improvement efforts.